Dr. Hackney STA Solutions pg 45

Dr. Hackney STA Solutions pg 45 - , 5) , (6 , 5) } ) = 12...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Chapter 4 Multiple Random Variables 4.1 Since the distribution is uniform, the easiest way to calculate these probabilities is as the ratio of areas, the total area being 4. a. The circle x 2 + y 2 1 has area π , so P ( X 2 + Y 2 1) = π 4 . b. The area below the line y = 2 x is half of the area of the square, so P (2 X - Y > 0) = 2 4 . c. Clearly P ( | X + Y | < 2) = 1. 4.2 These are all fundamental properties of integrals. The proof is the same as for Theorem 2.2.5 with bivariate integrals replacing univariate integrals. 4.3 For the experiment of tossing two fair dice, each of the points in the 36-point sample space are equally likely. So the probability of an event is (number of points in the event)/36. The given probabilities are obtained by noting the following equivalences of events. P ( { X = 0 ,Y = 0 } ) = P ( { (1 , 1) , (2 , 1) , (1 , 3) , (2 , 3) , (1 , 5) , (2 , 5) } ) = 6 36 = 1 6 P ( { X = 0 ,Y = 1 } ) = P ( { (1 , 2) , (2 , 2) , (1 , 4) , (2 , 4) , (1 , 6) , (2 , 6) } ) = 6 36 = 1 6 P ( { X = 1 ,Y = 0 } ) = P ( { (3 , 1) , (4 , 1) , (5 , 1) , (6 , 1) , (3 , 3) , (4 , 3) , (5 , 3) , (6 , 3) , (3 , 5) , (4 , 5) , (5
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: , 5) , (6 , 5) } ) = 12 36 = 1 3 P ( { X = 1 ,Y = 1 } ) = P ( { (3 , 2) , (4 , 2) , (5 , 2) , (6 , 2) , (3 , 4) , (4 , 4) , (5 , 4) , (6 , 4) , (3 , 6) , (4 , 6) , (5 , 6) , (6 , 6) } ) = 12 36 = 1 3 4.4 a. R 1 R 2 C ( x + 2 y ) dxdy = 4 C = 1, thus C = 1 4 . b. f X ( x ) = R 1 1 4 ( x + 2 y ) dy = 1 4 ( x + 1) &lt; x &lt; 2 otherwise c. F XY ( x,y ) = P ( X x,Y y ) = R x- R y- f ( v,u ) dvdu . The way this integral is calculated depends on the values of x and y . For example, for 0 &lt; x &lt; 2 and 0 &lt; y &lt; 1, F XY ( x,y ) = Z x- Z y- f ( u,v ) dvdu = Z x Z y 1 4 ( u + 2 v ) dvdu = x 2 y 8 + y 2 x 4 . But for 0 &lt; x &lt; 2 and 1 y , F XY ( x,y ) = Z x- Z y- f ( u,v ) dvdu = Z x Z 1 1 4 ( u + 2 v ) dvdu = x 2 8 + x 4 ....
View Full Document

Ask a homework question - tutors are online